KEUTUHAN WACANA "KATA PENGANTAR" DALAM SKRIPSI MAHASISWA - -, Mulyana; Setiawan, Teguh (Diksi, 2006)
Students' final paper generally has a page containing a preface which, interms of form and content, comprises an intact piece of discourse written with anarrative style. The number of paragraphs is in accordance with the contents andmessages the writer delivers to the reader. The paragraphs are designed to containwhat the writer wishes to express to certain respective parties: praises to God,information about the objective of a research the paper reports and the purpose ofwriting the paper, acknowledgements expressing gratitude, the writer's hopes, andinformation about the place, date, month, and year the paper writing is completed.Aspects of discourse completeness that stand out are cohesion, coherence, andtopicalization. Both formal and semantic aspects linguistically weave closeinterrelation forming an integrated and complete wholeness of the discourse.Keywords: discourse wholeness, paper preface